Uhl's anomaly. Differential diagnosis and indication for cardiac transplantation in an infant - Ikari,Nana Miura (2001)
We report the case of an 8-month-old female infant with Uhl's anomaly, who underwent successful cardiac transplantation. The clinical findings, complementary laboratory tests, anatomic findings, and differential diagnosis of the anomaly are discussed.